Exploring young women's perspectives of a targeted support programme for teenage parents. Issue 4 (16th July 2018) - McGeechan, Grant James; Baldwin, Michelle; Allan, Keith; O'Neill, Gillian; Newbury-Birch, Dorothy
Abstract : Context: Teenage parents and their children are at risk of poorer outcomes than older mothers, and their peers. Objective: Evaluate participants' experiences of a targeted teenage parent support programme. Design: A qualitative study was conducted to gain feedback from participants of a locally commissioned teenage parent support programme. Four focus groups were held with participants attending the programme in different areas of the county, and analysed using applied thematic analysis. Participants: Teenage mothers aged 16–19 years from vulnerable backgrounds (n=18) attending a teenage parent support programme in County Durham. Results: Two major themes emerged from the analysis focusing on factors influencing enrolment and continued engagement and how the programme leads to personal development for mother and child.The majority of participants felt that the group fostered a supportive environment and led to a reduction in social isolation. The provision of free transport and childcare onsite was seen as a key component of the service without which many would not have been able to attend. Discussion: The programme appeared effective at increasing the emotional and social capabilities of teenage mothers. It had a positive impact on parents' engagement in education and employment, as well as impacting on children's social development. Conclusions: Targeted support programmes have the ability to increase social and emotional capabilities of teenage mothers and their children. They can increase engagement in education and employment for teenage mothers. The provision of transport and free child care places can enhance engagement in such programmes.